Adsorpsi Zat Warna Methylene Blue Dengan Menggunakan Abu Sawit Sebagai Adsorben - Rizaldi Riski Irawan; Edy Saputra; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The industrial waste especially textile waste is one of the causes of environmental problems that require effective and efficient processing. Adsorption is a separation method that is simple, easy to operate, flexible, affordable cost anddoes not produce toxic products. The purpose of this study calculates theefficiency of decreasing the concentration of the colors contained in metyhleneblue dye and studying the adsorption capacity to variations in pH 2, 4, 6, and 8, adsorbent mass variation 1; 1,5; 2; and temperature variation 40º, 60º, and 80º. The maximum wavelength of the dye methylene blue 660 nm.The efficiency of 98,07 % decline in the highest concentration. Isothermcorresponding to methylene blue dye adsorption by spent bleaching earth isLangmuir isotherm with adsorption capacity to variations in pH of 4,592 mg/g, the adsorbent mass variation of 4,592 mg/g, the temperature variation of 3,565mg/g.Keywords: Adsorption, Methylene Blue, Fly Ash, Efficiency Decreased Concentration, Adsorption Capacity